Analisis Kepuasan Pengguna Sistem Informasi E-Campus Menggunakan Metode E-Servqual Dan Model Kano - Nurhadi, Muhammad; Hamzah, Muhammad Luthfi; Ahsyar, Tengku Khairil; Jazman, Muhammad (Forum Kerjasama Pendidikan Tinggi, 2022)
This study aims to identify the dimensions and service attributes that need to be improved, as well as improvements related to the quality of services provided by the e-campus system to students at UIN Mahmud Yunus Batusangkar. It also aims to identify the quality of services provided by the e-campus system to students. in order to provide advice or consideration to improve the quality of the e-campus system to the campus or developer, which in turn will produce a solution to improve the quality of the e-campus system for user satisfaction. The procedures used include 5 stages are planning, gathering information processing information analysis and the latest reporting review. The research results created calculations using e-servqual procedures of 0.92 ≤ 1, showing that the quality of the services provided could be said to be unable to fulfill students' expectations. If the level of performance is met, it will bring about a very large increase in user satisfaction. But if not fulfilled, it will reduce the level of satisfaction. Whereas the canoe model gets eight attributes included in the must-be category, eight one-dimensional attributes and six attractive attributes. The ranking level obtained is a source of attributes that are prioritized to be improved. Every attribute that has a very large negative value will also be less effective in achieving user satisfaction